Pengaruh Model Problem Solving Terhadap Kemampuan Pemahaman Konsep Matematik Siswa Sekolah Dasar - Misrina Misrina (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study aims to determine the effect of the ability to mathematical conseptual understanding of elementary school students using problem solving learning models. The research method used in this study was a quasi-experimental design with the non-equivalent groups pretest-posttest design. The sample set in this study was class V students, totaling 48 consisting of 24 experimental classes and 24 control classes. The results showed that the effect toward students’ conceptual understanding ability of experimental class students who studied with problem solving was better than the students’ conceptual understanding ability of control class who studied using direct learning models.